Vertical Characteristics of Potential PM2.5 Sources in the Urban Environment - Ho-Tang Liao; Yu-Chi Lai; Hsing Jasmine Chao; Chang-Fu Wu (Aerosol and Air Quality Research)
Abstract Exposure to urban air pollution, particularly fine particulate matter (PM2.5), is known to be harmful to human health. Source apportionment of urban PM2.5 provides information to develop effective control strategies, thus reducing the exposure concentrations and health risks. However, this is a challenging task in metropolitan areas where people live in high-rise buildings. To understand the vertical characteristics of air pollution sources in urban areas, a total of 114 vertically stratified PM2.5 samples were collected at six heights (1st, 7th, 10th, 13th, 17th, and 20th floors) of one building during the period between 19 October and 22 December 2020. Absorbance, 16 trace elements, 8 water-soluble ions, and water-soluble organic carbon on Teflon-membrane filters were measured. Positive Matrix Factorization was utilized to achieve the source apportionment analysis. Six source factors, including biomass burning/industry, traffic related, secondary aerosol, soil dust, contaminated road dust, and sea salt, were retrieved. During the sampling period, the major contributor to PM2.5 was secondary aerosol (28.8%), followed by biomass burning/industry (24.4%) and traffic related (13.3%). It should be noted that road traffic emissions (traffic related and contaminated road dust) accounted for 24.7%, making them the second largest contributor to PM2.5. Contributions of road traffic emissions significantly declined with height (29.3%–21.4%), which was in line with the findings in previous studies, and could explain the vertical variation of PM2.5 identified in this study. These findings help estimate the realistic exposure at different residential heights, consequently facilitating control strategy development.